Design and evaluation of biological gate circuits and their therapeutic applications in a model of multidrug resistant cancers - Soheili, Naeimeh; Eshghi, Mohammad; Emadi-Baygi, Modjtaba; Mirzaei, Seyed Abbas; Heidari, Razieh; Hosseinzadeh, Mehdi (Biotechnology letters, 2020)
Objectives Synthetic biology is primarily an emerging research field that consists of designing new synthetic gene circuits dedicated to targeted functions and therapies such as cancer therapy. In this study, a genetic logic NOT-IF gate is used to reduce the multidrug resistance and facilitate the malignant cancer therapy. MCF7 cancer cells were cultured in RPMI-1640 medium and transfected with lentiviral vectors including MDR1 gene and the corresponding shRNA against MDR1 with controllable promoters. Transcript levels and protein levels of MDR1 gene were quantified. Results Our results showed that when doxycycline (DOX) and sodium butyrate were present and IPTG was absent, these led to a 74,354-fold increase in MDR1 gene expression. Upon IPTG treatment, the MDR1 gene expression was not detected due to the lack of the inducer. In addition, following IPTG induction in the presence of DOX and sodium butyrate and expressing shRNA, there was a 75% reduction in MDR1 gene expression compared to those cells treated only with sodium butyrate and DOX. Conclusions We successfully designed and implemented the genetic logic NOT-IF gate at the transcriptional level using the inducible expression of both MDR1 drug resistance pump and its specific shRNA in MCF7 cancer cells, using the third generation lentiviral vectors.